A new perspective of hypothalamic disease: Shapiro's syndrome - Ren, Linan; Gang, Xiaokun; Yang, Shuo; Sun, Meixin; Wang, Guixia (Frontiers in Neurology, 2022)
Shapiro’s syndrome (SS) is characterized by spontaneous periodic hypothermia, hyperhidrosis and agenesis of the corpus callosum (ACC). It occurs regardless of age or sex. To date, less than 60 cases have been reported worldwide. Current knowledge of the disease is limited to clinical feature, while the pathogenesis and etiology are still controversial. In this paper, the clinical characteristics, pathological mechanism and possible etiology of the syndrome were reviewed to improve the understanding of clinicians.